Erfolgreiche Therapie der kutanen Leishmaniose mit simulierter Tageslicht-photodynamischer Therapie - Hobelsberger, Sarah; Krauss, Marie-Paloma; Bogdan, Christian; Aschoff, Roland (Hautarzt, 2021)
A 5-year-old Syrian boy , presented with a complex cutaneous leishmaniasis (CL) of the right ankle caused by Leishmania (L.) tropica. The patient received photodynamic therapy (PDT; 6 cycles with application of 5‑aminolevulinic acid and foil occlusion for 3 h). Due to pain during exposure to red light, exposure was continued with simulated daylight (sDL-PDT). The lesion healed with an atrophic scar. Due to fewer side effects and less pain, sDL-PDT seems to be a good therapeutic strategy for CL caused by L. tropica.
CRIS-Team Scopus Importer:2021-07-16
Keywords: 5‑Aminolevulinic acid; Child; Foil occlusion; Leishmania tropica; Simulated daylight photodynamic therapy